2007
DOI: 10.1183/09031936.00131106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genioglossus contraction on pharyngeal lumen and airflow in sleep apnoea patients

Abstract: The purpose of the present study was to quantify the mechanical effect of genioglossus stimulation on flow mechanics and pharyngeal cross-sectional area in patients with obstructive sleep apnoea, and to identify variables that determine the magnitude of the respiratory effect of tongue protrusion.The pressure/flow and pressure/cross-sectional area relationships of the velo-and oropharynx were assessed in spontaneously breathing propofol-anaesthetised subjects before and during genioglossus stimulation.Genioglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
83
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 35 publications
7
83
0
3
Order By: Relevance
“…In these prior studies, investigators scrutinized EEG and ECG signals to exclude responses associated with cortical or autonomic activation (13,18,19). Additional studies with implantable nerve cuff (13) and fine-wire electrodes have demonstrated responses to selective lingual muscle stimulation during sleep and anesthesia (13)(14)(15)(16)(17). The present study also screened for evidence of cortical and autonomic activation, and further required strict temporal synchrony between the stimulus burst and airflow response to exclude arousal responses from the analysis.…”
Section: Arousalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these prior studies, investigators scrutinized EEG and ECG signals to exclude responses associated with cortical or autonomic activation (13,18,19). Additional studies with implantable nerve cuff (13) and fine-wire electrodes have demonstrated responses to selective lingual muscle stimulation during sleep and anesthesia (13)(14)(15)(16)(17). The present study also screened for evidence of cortical and autonomic activation, and further required strict temporal synchrony between the stimulus burst and airflow response to exclude arousal responses from the analysis.…”
Section: Arousalsmentioning
confidence: 99%
“…Implantable HGNS systems have been developed to stimulate the hypoglossal nerve during inspiration, and recruit the lingual musculature, leading to decreases in pharyngeal collapsibility during sleep (14)(15)(16)(17). Motor activity protrudes the tongue, and mitigates airflow obstruction during sleep (18,19).…”
mentioning
confidence: 99%
“…Activation of the GG, the main tongue protrusor, has been shown in animal studies to reduce pharyngeal resistance and collapsibility by far more than all other upper airway dilators (15,16). Electrically induced tongue protrusion has been shown to reduce pharyngeal resistance during wakefulness (24), lower the critical pressure (Pcrit) during sleep and anesthesia (18,19), and enlarge the pharynx (19). However, despite its central role, electrically induced GG contraction resulted in rather modest effects on upper airway mechanics (i.e., collapsibility), with wide variations in response between subjects (18,19).…”
mentioning
confidence: 99%
“…Electrically induced tongue protrusion has been shown to reduce pharyngeal resistance during wakefulness (24), lower the critical pressure (Pcrit) during sleep and anesthesia (18,19), and enlarge the pharynx (19). However, despite its central role, electrically induced GG contraction resulted in rather modest effects on upper airway mechanics (i.e., collapsibility), with wide variations in response between subjects (18,19). Failure to stimulate adequate areas of the GG and hypotonia of the nonstimulated upper airway muscles were considered as possible explanations for the lack of response in some of the patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation